The Mound and the Malay Nusantara historic landscape - Baniyamin, Nurhaya; Zain, Mazarina; Ibrahim, Mansor (Palgrave Macmillan, Singapore, 2023)
The portico is the essence of tropical form and represents the quintessential architectural character of the South East Asian tropics. The variations of the verandah, ‘anjung’ and ‘serambi’, can be seen as the ‘permutations’ of the tropical portico. The portico can be broken down and mapped to unearth a corpus of frontage ‘layered’ layouts and configurations. In the discourse of tropical architecture, the portico is a part of public space and differs from the ‘balcony’, which remains an elemental attachment to form, rather than an inherent part of the main structure and space, evolving through centuries as a container of community life. This chapter represents a series of ‘open air’ deep spaces which occupy a range of frontages of palatial architecture in South East Asia. The focus on the palatial or aristocratic form stems from the fact that the ‘portico’, in the case of this complex building type, constitutes the traditional public realm, within which public events and transactions are played out in tropical Asian public life.